REKONTRUKSI KARAKTERISTIK BUDAYA ORGANISASI DI INDONESIA DALAM MENINGKATKAN KOMPETENSI SUMBER DAYA MANUSIA - Mulyaningsih Mulyaningsih (IKIP Siliwangi Bandung, 2020)
Human resources must be used as thoughts towards changing attitudes and views of the nation as a consequence of humans as individuals in their relations with the national and international community. Strategically Characteristics of Organizational Culture owned by Indonesian HR must be able to support the implementation of development progress through measurable capabilities by having organized entrepreneurial capacity that makes Indonesian HR a 'model of sharing' and agents of change from the reconstruction of values. the value contained in Pancasila as a noble value of the positive character possessed by the Indonesian people through the results of research studies at the Sundanese level, namely: